The Influence of First Aid Education on Knowledge Work Accidents in Students of SMK 4 Banda Aceh - Wulandari, Yulia; Mahruri Saputra; Eridha Putra; Maulida; Gadis Halizasia (Teewan Journal Solutions, 2025)
First aid is the initial action given to individuals who experience emergency conditions due to injury or accident, before receiving further medical treatment. A person's level of knowledge plays an important role in supporting the effectiveness of education regarding first aid for work accidents. Work accidents themselves can be caused by human factors or environmental factors. This study aims to analyze the effect of first aid education on increasing students' knowledge about work accidents. The method used is quantitative research with a pre-experimental design. The sampling technique used total sampling, with a total of 33 students as respondents. The study was conducted on March 10, 2025 using a questionnaire instrument. The results showed that before being given education, all students (33 people) had a low level of knowledge. However, after receiving education, all respondents experienced a significant increase in knowledge into the good category. Based on the results of the hypothesis test, a p value of 0.000 (<0.05) was obtained, which indicates that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that first aid education has a significant effect on increasing students' knowledge about work accidents.